2007
DOI: 10.1016/j.ijgo.2007.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal ultrasound assessment of the fetal head and the accuracy of vacuum cup application

Abstract: Intrapartum transabdominal ultrasound assessment of the fetal head position during the second stage of labor improves the accuracy of vacuum cup placement during vacuum extraction for prolonged second stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 11 publications
2
20
1
1
Order By: Relevance
“…Two small-scale studies had findings similar to ours. 21,31 A cohort study of 64 women reported an incorrect diagnosis rate of 27% for vaginal examination compared with ultrasound, with errors more likely with OP positions. 21 A randomised trial of 50 women undergoing vacuum extraction for prolonged second stage reported that cup placement was closer to the flexion point, and therefore more optimal, in the group assigned to ultrasound compared with vaginal examination only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two small-scale studies had findings similar to ours. 21,31 A cohort study of 64 women reported an incorrect diagnosis rate of 27% for vaginal examination compared with ultrasound, with errors more likely with OP positions. 21 A randomised trial of 50 women undergoing vacuum extraction for prolonged second stage reported that cup placement was closer to the flexion point, and therefore more optimal, in the group assigned to ultrasound compared with vaginal examination only.…”
Section: Discussionmentioning
confidence: 99%
“…21 A randomised trial of 50 women undergoing vacuum extraction for prolonged second stage reported that cup placement was closer to the flexion point, and therefore more optimal, in the group assigned to ultrasound compared with vaginal examination only. 31 The decision to delivery interval is an important consideration for instrumental delivery. 33 It was reassuring that the addition of an ultrasound scan as part of the assessment did not introduce a delay in delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cap must be placed at or close to the flexion point on the vertex. Ultrasound aided examination has been shown to detect this flexion point better than digital examination alone [Wong, 2007;Molina and Nicholides, 2010] …”
Section: Head Position For Vacuummentioning
confidence: 99%
“…In this study of vacuum extractions, incorrect cup placement was reported in about half of the procedures and an increase in neonatal injury from 5% for flexing median placement of the cup to 45% for deflexing paramedian application [23] . Wong et al [25] have demonstrated that the accuracy of vacuum cup placement prior to vacuum extraction can be improved using transabdominal ultrasonographic assessment of the fetal head position. They randomly allocated 50 women with prolonged second stage to either digital examination (n = 25) or digital examination together with transabdominal intrapartum ultrasound (n = 25) prior to vacuum extraction by the attending obstetrician.…”
Section: Ultrasound To Define Fetal Head Position Before Instrumentalmentioning
confidence: 99%